Ecosystem Services and Disservices Are Bundled in Simple and Diverse Cover Cropping Systems. Issue 1 (1st November 2017) - Finney, Denise M.; Murrell, Ebony G.; White, Charles M.; Baraibar, Barbara; Barbercheck, Mary E.; Bradley, Brosi A.; Cornelisse, Sarah; Hunter, Mitchell C.; Kaye, Jason P.; Mortensen, David A.; Mullen, Christina A.; Schipanski, Meagan E.
Abstract : Core Ideas: Cover crop monocultures and mixtures support multiple ecosystem services. Service interactions can lead to bundling, or co‐occurrence, of certain services. Service interactions also create trade‐offs among services and disservices. Cover crop mixtures can mitigate disservices to increase multifunctionality. Agroecosystems are increasingly expected to provide multiple ecosystem services. We tested whether and how cover crop selection (identity and number of species) affects provisioning of multiple services (multifunctionality). In a 3‐yr study of 10 cover crop treatments and eight ecosystem services, certain services consistently co‐occurred. One such service "bundle" included cover crop biomass production, weed suppression, and nitrogen retention. Another set of bundled services included cash crop production, nitrogen supply, and profitability. We also identified trade‐offs: as some services increased, other disservices arose, limiting multifunctionality. However, functionally diverse mixtures ameliorated disservices associated with certain monocultures, thereby increasing cover crop multifunctionality.